The nucleotide‐bound/substrate‐bound conformation of the Mycoplasma genitalium DnaK chaperone. (14th April 2018) - Adell, Maria; Calisto, Bárbara M.; Fita, Ignacio; Martinelli, Luca
Abstract: Hsp70 chaperones keep protein homeostasis facilitating the response of organisms to changes in external and internal conditions. Hsp70s have two domains—nucleotide binding domain (NBD) and substrate binding domain (SBD)—connected by a conserved hydrophobic linker. Functioning of Hsp70s depend on tightly regulated cycles of ATP hydrolysis allosterically coupled, often together with cochaperones, to the binding/release of peptide substrates. Here we describe the crystal structure of the Mycoplasma genitalium DnaK ( Mg DnaK) protein, an Hsp70 homolog, in the noncompact, nucleotide‐bound/substrate‐bound conformation. The Mg DnaK structure resembles the one from the thermophilic eubacteria DnaK trapped in the same state. However, in Mg DnaK the NBD and SBD domains remain close to each other despite the lack of direct interaction between them and with the linker contacting the two subdomains of SBD. These observations suggest that the structures might represent an intermediate of the protein where the conserved linker binds to the SBD to favor the noncompact state of the protein by stabilizing the SBDβ‐SBDα subdomains interaction, promoting the capacity of the protein to sample different conformations, which is critical for proper functioning of the molecular chaperone allosteric mechanism. Comparison of the solved structures indicates that the NBD remains essentially invariant in presence or absence of nucleotide. Abstract : Interactive Figure 1, Interactive Figure 2